Política habitacional e inserção urbana: um estudo sobre a cidade de Quixadá/Ce - Laurentino, D’Ávila de Melo (2023)
Social housing (HIS) is a pressing challenge in Brazilian urban areas, because as cities go through a process of expansion associated with the commodification of urban land, the most visible result is an increase in precariousness and socio-spatial inequalities. This dissertation explores the intricate relationship between the production of HIS and its urban insertion, that is, the dynamics of integration of popular housing constructions into existing urban infrastructures. Urban insertion is relevant in contexts of urban planning and housing policy because it reduces pressure on poverty in cities, improves access to services and opportunities, in addition to contributing to the reduction of environmental impacts. This research has as a case study the examination of the production of popular housing complexes in the municipality of Quixadá/CE, from 1994 to 2018. It is a medium-sized municipality, which underwent a demographic inversion from rural to urban population from the 1990s onwards. Six housing complexes built by different public policy initiatives throughout the period mentioned were identified. This research focuses on explaining and analyzing the urban insertion of these complexes, from their origin to the current location characteristics of the urban form. The methodological approach is exploratory-descriptive in nature combined with the use of bibliographic review, documentary analysis, field surveys and interviews. The results achieved indicate that older housing complexes are in a more favorable situation of urban insertion, with better mobility conditions and accessibility to public services and equipment. A different situation occurs with the most recent HIS production in the municipality, the Rachel de Queiroz condominium (2018), a large project linked to the Minha Casa Minha Vida Program, built outside the urban perimeter and with evident signs of spatial segregation, social exclusion and urban violence.